Tectonometamorphic evolution of a subduction plate interface at the base of the Mirdita Ophiolite (Bajram Curri, northeastern Albania) - Madeline Richter; Kilian Pollok; Kujtim Onuzi; Kamil Ustaszewski (Swiss Journal of Geosciences)
Abstract The Western Vardar ophiolite, a thrust sheet of oceanic crust and mantle obducted onto the Adriatic passive margin in the Late Jurassic, crops out along the entire Balkan Peninsula. The Mirdita Ophiolite forms the northern Albanian segment of this unit. In northeast Albania near Bajram Curri, a 200–700 m thick metamorphic sole is preserved at its base. The assembly of obducted mantle rocks and metamorphic sole constitutes a plate interface that formed during the intraoceanic subduction stage preceding obduction; we call this a fossil intraoceanic plate interface in this paper. This setting allows to study the interrelated tectonometamorphic evolution and rock-water interaction between the subducted and exhumed metamorphic sole and concomitant mantle wedge serpentinization in the overlying units. We combined detailed lithological and structural mapping with micro-scale analyses along this plate interface. Three tectonic units were distinguished. Mylonitic harzburgites overlie a tightly folded, tectonised subophiolitic mélange along a SE-dipping contact that defines the fossil intraoceanic plate interface. The tectonised subophiolitic mélange itself was separated into a structurally lower non-metamorphic broken formation and a higher metamorphic sole, separated by an isoclinally folded thrust. Within the metamorphic sole, the temperature and degree of deformation increase towards the structural top. Shear sense indicators in calcschists of the metamorphic sole show top to the west transport of the overriding units. All metamorphic sole lithologies were overprinted at lower greenschist-facies conditions, reflecting their exhumation from intraoceanic subduction. Corresponding microstructures indicate mineral growth at isotropic stresses, suggesting that deformation migrated into structurally lower, frontally accreted non-metamorphic units of the sub-ophiolitic mélange marking the start of obduction onto the passive Adriatic margin. Ongoing westward transport led to folding of the entire sub-ophiolitic succession. Harzburgites are more deformed towards the plate interface, forming a mylonitic fabric. There, harzburgites contain accessory Cr-rich spinel and the foliation is dissected by multiple generations of veins containing serpentine and magnetite. Vein density is highest along the plate interface and decreases up-section, suggesting that serpentinisation was triggered by devolatilisation reactions in the sediments of the metamorphic sole that were subducting below the harzburgites, and the upwards migration of volatiles into the overlying mantle wedge.